D-cyclins Repress Apoptosis in Hematopoietic Cells by Controlling Death Receptor Fas and its Ligand FasL - Choi, Yoon Jong (2014)
D-type cyclins (D1, D2 and D3) are components of the mammalian core cell cycle machinery and function to drive cell proliferation. Here we report that D-cyclins perform a rate-limiting anti-apoptotic function in vivo. We found that acute shutdown of all three D-cyclins in bone marrow of adult mice resulted in massive apoptosis of all hematopoietic cell types. We demonstrate that adult hematopoietic stem cells are particularly dependent on D-cyclins for survival, and they are especially sensitive to cyclin D loss. Surprisingly, we found that the anti-apoptotic function of D-cyclins also operates in quiescent hematopoietic stem and progenitor cells. Our analyses revealed that D-cyclins repress the expression of the death receptor Fas and its ligand, FasL. Acute ablation of D-cyclins upregulated these pro-apoptotic genes, and led to Fas- and caspase 8-dependent apoptosis. These results reveal an unexpected function of cell cycle proteins in controlling apoptosis in normal cell homeostasis.